Teoria della nascita e castrazione umana. Due presentazioni - Vari, Autori (Il sogno della farfalla, 2012)
We publish the transcripts of the talks given and the debates which ensued during the two book launches of Massimo Fagioli’s book Teoria della nascita e castrazione umana (The birth theory and human castration), held on 13th April and 12th May 2012, respectively in a Roman bookshop and at the Turin International Book Salon. Published for the first time in 1975, Teoria della nascita e castrazione umana was the last book of Fagioli’s trilogy, which started in 1972 with The death drive and knowledge, followed by La marionetta e il burattino (1974) laying down the theoretical basis which would give rise, a number of months later, to the collective analysis. And it is the very experience of the collective analysis which is one of the themes of the talks given, which bring to light in the wake of recent scientific discoveries, the scientific content of the book and its implications for therapeutic practice.